INCREASING CULTURE KNOWLEDGE AND GROWING ENVIRONMENTAL AWARENESS ATTITUDE OF JUNIOR SECONDARY SCHOOL STUDENTS THROUGH CHEMISTRY LOCAL CONTENT PROGRAM - Basuki, Ari (Global Science Education Journal, 2020)
The purpose of this research are increase of culture knowledge and grow of  environmental awareness attitude junior secondary school students at chemistry learning, by applying of chemistry local content program based on the ?Orang Laut? culture. Research conduct used quasi-experiment method. Research subjects were 8th grade students in Tanjungpinang city that consist of 99 and 94 students on experiment and control groups, respectively. Score of culture knowledge and environmental awareness attitude collected by validated test and questionnaire instruments, respectively. Pretest and posttest culture knowledge scores used to calculate of normalized gain (N-gain) average of experiment and control groups. Average score of environmental awareness attitude used to identify of student environmental awareness attitude growth after chemistry learning on the experiment  group. To compare the increasing of  culture knowledge on the experiment and control groups conduct by statistical t-test with ?=0,05. The research result indicated that applying of chemistry local content program based on the ?Orang Laut? culture at chemistry  learning could  increase of culture knowledge junior secondary school students better than conventional chemistry learning and growth of student environmental awareness attitude. The difference of  culture knowledge increased on the  experiment and control groups was significant ( tcalc = 10,023; p=0,000) with average of  N-gain percent  respectively 46 and 20 in the middle and low categories. Average score of student environmental awareness attitude in good criteria at 3,8 point.